The effect of throwing movement in various run-up speeds for javelin throwers - Aoyama, S.; Kanazawa, N.; Aoyama, T.; Tsunoda, N. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The javelin throw involves complex movements that run-up and throwing also run-up is an integral part of the javelin throw. Most studies of javelin throwing performance are final phase such as release parameters. However, no study has focused on between run-up and movement speed of javelin throw. Therefore the purpose of this study was to clarify the effect of throwing movement speeds in various run-up speeds for javelin throw. Methods: The subjects were seven male right-handed javelin throwers (age: 21.3±2.1yrs, height: 174.9±5.9cm, body weight: 80.6±6.0kg, PB: 66.97±3.95m). All the subjects performed for total 6 throws. Details were two throw which same run-up speed as competition (CT), two 80% of CT (80%t) and two 60% of CT (60%t) for recorded best throw from each throw. The run-up speed was measured using by Speed meter (VINE, Japan) with attached to the waist. Throwing movement velocities of during the run-up were measured from the front and right side of the throwing area by video cameras operating at 60 frames per seconds and set at 1/250s shutter speed. It was used in DLT to 3-D coordinates of the digitized body and javelin parts (movement velocity of javelin: JV, movement velocity of right wrist: WV, movement velocity of right elbow: EV, movement velocity of right shoulder: SV). Results: The results of this study were: CT was significantly higher than 80%t and 60%t. A significant correlation was observed between various run-up speed and javelin throw performance in all the throws (r=0.534, p<0.05). Also, CT of javelin throw performance was significantly higher than 60%t of javelin throw performance. However, no significant differences in JV were observed between CT and 80% and 60%. Moreover, there were no significant differences between various run-up speed and WV, EV, SV. Discussion: The run-up speed is one of the important contributions to javelin throw. In this study, there were no differences between movement velocity of JV, WV, EV and SV in various run-up speeds. In addition, there were no significant between various run-up speed and JV, WV, EV, SV. This means that it does not need to throw run-up of maximum speed to daily training of javelin throw technique. Therefore, run-up speed of 80% and 60% are good way to develop the correct movement and skill of javelin throw training. From these results, it was suggested that it is important factor to consideration for prevented injury of shoulder, elbow and wrist that can be expectation of better javelin throw technique and performance.